Determination of Hypericin in Hypericum perforatum (St. John's Wort) Using Classical C18 and Pentafluorophenyl Stationary Phases: Contribution of Pi–Pi Interactions to High-Performance Liquid Chromatography (HPLC). (24th July 2019) - Doležal, Rafael; Houdková, Iva; Kalász, Huba; Andrýs, Rudolf; Novák, Martin; Maltsevskaya, Nadezhda V.; Karásková, Natálie; Kolář, Karel; Novotná, Eva; Kuča, Kamil; Žďárová Karasová, Jana
Abstract: Hypericin is one of the most important bioactive substances present in Hypericum perforatum (Saint John's Wort), which exhibits various biological activities such as inhibition of neuronal processes coupled with transmission of serotonin, dopamine, gamma-amino butyric acid and L -glutamine. This red-colored derivative of anthraquinone contains six benzene cycles and four hydroxy groups that polarize electron density in the conjugated double bond system and enable the molecule to act as a Lewis base in charge-transfer complexes. In this study, four stationary phases modified by the pentafluorophenyl group were selected to investigate the contribution of π-π interactions to the improvement of hypericin separation in comparison to the separation provided with a classical C18 based chromatographic column. In order to develop a suitable gradient chromatographic method for the quantification of hypericin, normal, polar organic and reverse elution modes were evaluated using high-performance liquid chromatography with ultraviolet-visible and mass spectrometry detection. It was disclosed in the analyses that the pentafluorophenyl stationary phase can separate hypericin from hyperforin, which was not possible to achieve with the C18 based stationary phase. The best analytical method found, employing the pentafluorophenyl stationary phase, showed sufficient linearity, accuracy and precision and was used for the determination of hypericin in Saint John's Wort.